1994
DOI: 10.1136/bjo.78.4.266
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous dysplasia of the orbit.

Abstract: Twelve patients with fibrous dysplasia of the orbit are reviewed and the ophthalmic findings described. Three case histories are presented in detail. Six patients were managed conserva-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 26 publications
0
30
0
1
Order By: Relevance
“…FD was first described by von Recklinghausen in 1891 in McCune-Albright Syndrome (MAS) with genetically linked with the GNAS1 gene somatic mutation, however in 1938 Lichtenstein coined the term fibrous dysplasia in its monostotic and polyostotic character [1][2][3]. FD comprises 2.5% of all bony tumors and 7.5% of benign bony lesions [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…FD was first described by von Recklinghausen in 1891 in McCune-Albright Syndrome (MAS) with genetically linked with the GNAS1 gene somatic mutation, however in 1938 Lichtenstein coined the term fibrous dysplasia in its monostotic and polyostotic character [1][2][3]. FD comprises 2.5% of all bony tumors and 7.5% of benign bony lesions [7].…”
Section: Discussionmentioning
confidence: 99%
“…FD typically involves the skull, long bones, and ribs in which there is replacement of normal bone marrow with fibro-osseous tissue manifesting as a painless asymmetric bony enlargement [1,3,6]. FD is monostotic in 70-80% of cases, while 20-30% are polyostotic, and only 10% of overall cases are found to be in the craniofacial region, most commonly in the maxilla and frontal bone [1,2,6]. The monostotic variant usually presents in the craniofacial bones, femur, tibia and ribs, while the polyostotic form typically presents in the femur, tibia and pelvis with common complaints of pain associated with recurrent fractures [8].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Criteria for study population inclusion were histopathologic diagnosis of CFD, radiologically confirmed optic canal narrowing, pre-and post-treatment visual status (based on visual fields and visual acuity), and .4 months of follow-up. The included studies are listed in Tables S1, S2, S3 (supplementary material) [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33]. Follow-up included periodic (6-12 months) radiological imaging with CT and MRI as well as ophthalmologic exams.…”
Section: Participantsmentioning
confidence: 99%